First use of the 137Cs techniques in Nigeria for estimating mediumterm soil redistribution rates on cultivated farmland - Junge, B.; Mabit, L.; Dercon, G.; Walling, D.E.; Abaidoo, Robert C.; Chikoye, David; Stahr, Karl (Elsevier, 2010)
Soil erosion is a serious problem in the forest-savanna transition zone or derived savanna of West Africa and Nigeria and needs to be reduced to maintain soil quality and to ensure food security. In 2007, the use of the fallout radionuclide 137Cs as a tracer for estimating the magnitude of medium-term (40–50 years) rates of soil redistribution was tested at a research station in Ibadan, Nigeria, to investigate, for the first time, its applicability in the derived savanna of West Africa.Because of the traditional tillage practice for cassava cultivation of creating downslope oriented ridges and furrows during the annual ploughing, there was a need to adapt the 137Cs approach to these specific condition. The mean inventory was determined for cores collected from both ridges and furrows at different positions down the slope and this value was used to estimate the downslope variation in the longer term soil redistribution rate. The mean 137Cs reference inventory obtained for an undisturbed site was 568 ± 138 Bq m−2. The average inventory for the upper slope of the cassava field (423 ± 323 Bq m−2) was generally lower than the average inventory for the middle slope (509 ± 166 Bq m−2) and for the lower slope (606 ± 245 Bq m−2) and these results provided clear evidence of the downslope movement of soil. The mean 137Cs inventory for the study area within the cassava field (496 ± 273 Bq m−2) was 13% lower than the reference inventory, indicating that some of the soil mobilised and redistributed by erosion had been exported beyond the field.Using 137Cs data set and the conversion model mass balance model 2 (MBM2), the gross erosion rate from the cultivated site was estimated to be 18.3 t ha−1 year−1 and the net erosion rate 14.4 t ha−1 year−1, providing a sediment delivery ratio of 78%. These estimates are comparable to the rates generated by conventional soil loss measurements made close to the study site. The study demonstrates that the 137Cs technique can be successfully used to obtain data on medium-term soil redistribution in the derived savanna of Nigeria, and that it could be a useful tool for supporting the improvement of soil conservation on farmland in West Africa.